Difference between revisions of "009A Sample Final 1, Problem 7"
Jump to navigation
Jump to search
Line 3: | Line 3: | ||
::::::<math>x^3+y^3=6xy.</math> | ::::::<math>x^3+y^3=6xy.</math> | ||
− | <span class="exam">a) Using implicit differentiation, compute  <math style="vertical-align: -12px">\frac{dy}{dx}</math>. | + | ::<span class="exam">a) Using implicit differentiation, compute  <math style="vertical-align: -12px">\frac{dy}{dx}</math>. |
− | <span class="exam">b) Find an equation of the tangent line to the curve <math style="vertical-align: -4px">x^3+y^3=6xy</math> at the point <math style="vertical-align: -5px">(3,3)</math>. | + | ::<span class="exam">b) Find an equation of the tangent line to the curve <math style="vertical-align: -4px">x^3+y^3=6xy</math> at the point <math style="vertical-align: -5px">(3,3)</math>. |
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
Line 49: | Line 49: | ||
::<math>3x^2-6y=\frac{dy}{dx}(6x-3y^2).</math> | ::<math>3x^2-6y=\frac{dy}{dx}(6x-3y^2).</math> | ||
|- | |- | ||
− | |We solve to get | + | |We solve to get |
+ | |- | ||
+ | | | ||
+ | ::<math style="vertical-align: -17px">\frac{dy}{dx}=\frac{3x^2-6y}{6x-3y^2}.</math> | ||
|} | |} | ||
Revision as of 11:17, 18 April 2016
A curve is defined implicitly by the equation
- a) Using implicit differentiation, compute .
- b) Find an equation of the tangent line to the curve at the point .
Foundations: |
---|
1. What is the result of implicit differentiation of |
|
2. What two pieces of information do you need to write the equation of a line? |
|
3. What is the slope of the tangent line of a curve? |
|
Solution:
(a)
Step 1: |
---|
Using implicit differentiation on the equation we get |
|
Step 2: |
---|
Now, we move all the terms to one side of the equation. |
So, we have |
|
We solve to get |
|
(b)
Step 1: |
---|
First, we find the slope of the tangent line at the point |
We plug into the formula for we found in part (a). |
So, we get |
|
Step 2: |
---|
Now, we have the slope of the tangent line at and a point. |
Thus, we can write the equation of the line. |
So, the equation of the tangent line at is |
|
Final Answer: |
---|
(a) |
(b) |